Cronobacter sakazakii growth on different types of naso-gastric tubing / Siti Norbaizura Md Zain and Steve Flint - Md Zain, Siti Norbaizura; Flint, Steve (Universiti Teknologi MARA, Negeri Sembilan, 2013)
Cronobacter sakazakii (C. sakazakii) is a ubiquitous environmental contaminant most notable for being associated with the deaths of neonates fed infant formula via naso-gastric tubing. Sixteen isolates from different origins were screened for their potential to form bioflim using a microtitre plate assay. All clinical isolates formed strong biofilm while environmental isolates formed biofilms of mixed strength. Growth on three different types (silicone, polyvinyl chloride (PVC) and polyurethane) of naso-gastric tubing was monitored over 24 h. Clinical, dairy and environmental isolates were able to form biofilm on the three different materials of infant feeding tubes but initial attachment and growth was slow on the silicone tubing compared with the other two types of tubing. Silicone tubing appeared to be the best choice for premature babies that need feeding using feeding tubes, as it was slow to become colonised compared with the PVC and polyurethane tubing.